Effect of reducing rates of NPK, ZA, and KCl fertilizers on the growth and yield of shallot in multiple cropping system in Bantul - Karsidi Karsidi; Endang Sulistyaningsih; Didik Indradewa; Budiastuti Kurniasih (Jurnal Ilmu Pertanian, 2020)
The intensive application of synthetic/inorganic fertilizer on shallot cultivation tends to contaminate the environment and reduce soil quality. Meanwhile, the decrease of farmland area has been a limiting factor in increasing shallot production. Shallot farmers in Bantul District, D. I. Yogyakarta, commonly combine organic and inorganic fertilizers. Therefore, an alternative technology to sustain the production of shallot is through the application of fertilizer at the right rates and  the practice of multiple cropping system. The objective of this research was to determine the growth and yield of shallot as affected by the reduced rates of inorganic fertilizer in multiple cropping systems. This research was conducted from August to November 2016 in Srigading Village, Sanden Sub-District, Bantul District, D. I. Yogyakarta. The research was arranged in a split plot design with three replications. The main plot was cropping system consisting of monoculture system (shallot) and multiple cropping system (shallot – chili). The subplot was fertilizer rates consisting of 100 % as control, 50 %, and 25 %. The results of this research showed that multiple cropping system did not decrease the growth and yield of shallot. Likewise, reducing inorganic fertilizer rates to 50% of control did not decrease shallot yield. However,  the inorganic fertilizer rate of 25% significantly decreased shallot yield to 12.15 %.